Letalidad por infarto agudo del miocardio en Cuba, 1999-2008. Acute myocardial infarction lethality in Cuba, 1999-2008. - Alfredo F. Dueñas Herrera; Lorenzo Llerena Rojas; Ramón Suárez Medina; Reinaldo de la Noval García; Yannela Y. Ortega Torres; Nuris B. Armas Rojas (ECIMED, 2011)
Introduction The acute myocardial infarction constitutes one of the first causes of death inthe world and in Cuba, it's distribution and tendency are ignored in the countryin the last years.Objective To determine the lethality of the acute myocardial infarction in Cuba, 1999-2008.Method A descriptive traverse study was carried out. Universe the total population over25 years old. The data were obtained from the registrations of the NationalStatistical Direction and the lethality rates were calculated. The variables usedwere the age, the sex, the place of death, the cause of death, the morbidityand the deceaseds. For the statistical analysis, rates were used and the generaltendency was calculated and for sex, the model was adjusted using exponentialsmoothing with two parameters.Results The lethality diminished in the five year period 2004-2008. The province withthe highest out of hospital lethality was Havana province.Conclusions The lethality stays high during the whole studied period.